Diagnosis of Learning Difficulties in the Field of Social Adaptation in Younger Schoolchildren - T.A. Egorenko; A.V. Lobanova; N.P. Radchikova (Moscow State University of Psychology and Education, 2023)
The work is the result of studying the difficulties in teaching younger schoolchildren in the field of social adaptation. The materials of an empirical study obtained on a sample (N=2030) of students aged 9-11 years in various regions of the Russian Federation (Republic of Tatarstan (20,5%), Lipetsk Region (16,5%), Volgograd Region (20,0%), Chuvash Republic (22,4%), Samara Region (20,5%)) are presented. The method "Strengths and difficulties" by R.N. Goodman (SST) was used, which allows to assess behavior, emotional sphere and relationships with peers, the method of self-assessment and the level of claims by Dembo-Rubinstein modified by A.M. Prihozhan and the Scale of apparent anxiety CMAS by J. Taylor in the adaptation of A.M. Prihozhan. The results obtained make it possible to say that the difficulties of establishing cooperative or friendly relations with peers, rejection by peers, aggressiveness towards others, irritability, difficulty or unwillingness to follow the rules of behavior are the most characteristic for younger schoolchildren. In girls of primary school age, emotional difficulties come to the fore, i.e. they are more susceptible to stress and its manifestations, anxiety and fears, while girls are more prone to manifestations of voluntary behavior designed to benefit another person and society as a whole, adherence to generally accepted rules, attentiveness to others.